Deconstructing Fairy Tale Binaries: A Comparative Reading of Grimm’s Snow White and Gaiman’s Snow, Glass, Apples - Gibran Muhammad Putra; Agry Pramita; Andang Saehu (Lingua Susastra, 2026)
Fairy tales function as cultural narratives that transmit moral values, yet their meanings remain open to reinterpretation through adaptation. While the Brothers Grimm's Snow White establishes seemingly fixed distinctions between innocence and evil, Neil Gaiman's Snow, Glass, Apples challenges these assumptions by offering an antithetical narrative perspective. This study employs Jacques Derrida's theory of deconstruction and Julia Kristeva's theory of intertextuality to examine how the binary oppositions of good/evil and love/lust are constructed and destabilized across three shared narrative fragments: Snow White's relationship with the Queen, her encounter with the dwarves, and her relationship with the Prince. Through a qualitative descriptive method and close comparative reading, the findings reveal three key instabilities. First, the Grimm text hierarchically privileges passivity, submission, and domesticity as markers of goodness, yet contains an internal contradiction wherein agency is demonized when exercised by the Queen. Second, Gaiman's rewriting exposes these contradictions by reinterpreting the Queen's actions as protective statecraft, reframing the dwarves as predatory beings, and unmasking the Prince's romantic devotion as physical obsession. Third, the study demonstrates that these binaries are not stable moral truths but ideologically constructed narratives sustained by selective storytelling. Theoretically, this research advances deconstructive literary criticism by showing how paired narratives function as intertextual doubles that expose suppressed contradictions, proving that fairy-tale meanings are continuously reconstructed through dialogue between texts. This study contributes to critical fairy tale studies by illustrating how postmodern retellings operate as literary criticism, destabilizing inherited hierarchies and inviting readers to reconsider the ideological assumptions embedded within canonical tales.